Lead-free thermal sensitive ceramic with high Curie temperature and low resistance and preparation method of lead-free thermal sensitive ceramic
By using solid phase reaction method and two-stage heating hydrothermal reaction method in BaTiO3-based lead-free PTCR ceramic materials to synthesize powders, and through ball milling, granulation and pressing, the problem of insufficient uniformity of the electrical properties of the ceramic materials due to chemical composition when sintered in an air atmosphere is solved, and ceramic materials with low room temperature resistivity and high Curie temperature are achieved, which are suitable for large-scale production.
Patent Information
- Application Number
- CN202411976989.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, when BaTiO3-based lead-free PTCR ceramic material is sintered in an air atmosphere, its electrical properties are affected by the problems of insufficient chemical composition uniformity and insufficient dispersion, resulting in a significant increase in room temperature resistivity and making it difficult to apply.
The (Ba1-xLax) TiO3 powder was synthesized by solid phase reaction method and the two-stage heating hydrothermal reaction method, and the (Ba1-x-yLax (Bi0.5Na0.5)Y)(Ti0.9996Mn0.0004)O3 ceramic material was formed by ball milling, granulation and pressing to ensure the uniformity and dispersion of chemical composition.
The BaTiO3-based lead-free PTCR ceramic material that is sintered in an air atmosphere has low room temperature resistivity and high Curie temperature, has good electrical properties, and is suitable for large-scale production.
Smart Images

Figure CN119638406A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic ceramic components, in particular to a high Curie temperature, low resistance, lead-free thermistor ceramic and a preparation method thereof. Background Art
[0002] Barium titanate (BaTiO3)-based positive temperature coefficient resistor (PTCR) ceramic materials, due to their unique resistance-temperature characteristics, can be used to manufacture various automatic constant temperature heating elements, starting switch elements, overcurrent and overheating protection elements, and temperature sensors for thermal information sensing, etc. They are widely used in the fields of frequency converters for household appliances, pre-charging and charging piles for new energy vehicles, and various motors. In recent years, the rapid development of new energy vehicles and power electronic systems requires thermistor components to have higher operating temperatures. For barium titanate-based PTCR ceramic materials, the temperature at which their resistance rises sharply is at the Curie temperature ( T c ~120 °C), so increasing the Curie temperature is a prerequisite for expanding the use of barium titanate-based PTCR ceramic materials at relatively high temperatures. T C >120 °C barium titanate-based PTCR ceramic materials are usually prepared by adding lead oxide (PbO or Pb3O4) or lead titanate (PbTiO3, T c =390 °C) to obtain a high Curie temperature. However, Pb-containing barium titanate-based PTCR ceramic materials may cause environmental pollution during production and waste treatment, so the development of lead-free barium titanate-based PTCR thermistor ceramic materials with high Curie temperature has become a major development trend.
[0003] (Bi 0.5 Na 0.5 )TiO3 (BNT) is a kind of material with a relatively high Curie temperature ( T C= 320 ℃) can form a solid solution with BaTiO3 and increase its Curie temperature. In 2005, Takeda et al. found that doping with 5 mol% BNT can increase the Curie temperature of BaTiO3 to about 170 ℃ (Applied Physics Letters, 2005, 87(10): 102–104), which set off a boom in the development of lead-free barium titanate-based PTCR ceramics. A large number of research results show that doping BaTiO3 with BNT can increase the Curie temperature of BaTiO3-based PTCR ceramics, but the room temperature resistivity also increases significantly. When the BNT content exceeds 2 mol%, BaTiO3-based ceramics sintered in air atmosphere cannot even be semiconductorized, so it is difficult to use in practice. At present, lead-free PTCR ceramics with relatively good comprehensive performance need to be sintered in a reducing atmosphere and then oxidized. The preparation process is sensitive and not suitable for mass production of PTCR ceramics. Therefore, how to prepare BaTiO3-based lead-free PTCR ceramics with good PTCR comprehensive properties by sintering in air atmosphere remains an unresolved technical problem.
[0004] At present, the preparation of BNT-doped BaTiO3-based lead-free PTCR ceramics mostly adopts the traditional solid-phase reaction method to synthesize ceramic powders. Its advantages are mature technology, simple process and low cost. However, the ceramic powders synthesized by the solid-phase reaction method are often not fully dispersed and the chemical composition is not uniform, which affects the electrical properties of the PTCR ceramics after sintering.
[0005] If a trace amount of BNT is doped into BaTiO3-based PTCR ceramics, its Curie temperature can be increased without significantly increasing the room temperature resistivity, and good PTCR comprehensive performance can be achieved. However, it is necessary to overcome the problem of uneven chemical composition of ceramic powders synthesized by solid phase reaction method. Summary of the invention
[0006] The present invention provides a high Curie temperature and low resistance lead-free thermistor ceramic and a preparation method thereof, which solves the problem that ceramic powder synthesized by a solid phase reaction method in the preparation of BaTiO3-based lead-free PTCR ceramic materials in the prior art is not sufficiently dispersed and the chemical composition is not uniform, thereby affecting the electrical properties of the sintered PTCR ceramic.
[0007] The first aspect of the present invention provides a high Curie temperature and low resistance lead-free thermistor ceramic, the chemical formula of which is (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004)O3; where the value range of x is 0.001 ≤ x ≤0.004, and the value range of y is 0.001 ≤ y ≤ 0.0075.
[0008] The second aspect of the present invention provides a method for preparing the above-mentioned high Curie temperature and low resistance lead-free thermistor ceramic, comprising the following steps: Step 1: Using BaCO3, TiO2, and La2O3 as raw materials, a solid phase reaction synthesis method was used to prepare (Ba 1-x La x )TiO3 powder; Step 2: Using Bi(NO3)3·5H2O, Ti(OC4H9)4 and NaOH as raw materials, a two-stage heating hydrothermal reaction method was used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder; Step 3: Follow (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio Weigh the (Ba 1-x La x )TiO3 powder, (Bi 0.5 Na 0.5 )TiO3 powder and Mn(NO3)2, and mixed with AST powder and added with anhydrous ethanol for ball milling, and then dried and ground; Step 4: adding polyvinyl alcohol and liquid paraffin to the powder ground in step 3 for granulation, and placing the granulated powder into a mold and pressing it into a green body; Step 5: Place the green body obtained in step 4 into a box furnace for debinding and sintering to obtain (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
[0009] Preferably, in step 1, the solid phase reaction synthesis method is used to prepare (Ba 1-x La x )TiO3 powder process is: according to (Ba 1-x La x)TiO3 stoichiometric ratio, weigh the raw material, and put the raw material and anhydrous ethanol into a ball mill at a volume ratio of 1:1, and after ball milling, place the slurry in an oven to dry, grind, sieve and calcine. The calcination temperature is 1200~1300℃, the heat preservation time is 2 hours, and then cooled to room temperature with the furnace to obtain (Ba 1-x La x )TiO3 powder.
[0010] Preferably, in step 2, the two-stage heating hydrothermal reaction method is used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder process is as follows: according to the molar ratio of Bi:Ti = 1:2, weigh Bi(NO3)3·5H2O and Ti(OC4H9)4, dissolve Bi(NO3)3·5H2O in dilute nitric acid solution to obtain solution a; dissolve Ti(OC4H9)4 in anhydrous ethanol and add it to solution a to obtain solution b; dissolve NaOH in deionized water at a concentration of 6-14 mol / l to obtain NaOH solution; add solution b to the NaOH solution to obtain a precursor solution; put the precursor solution into a stainless steel reactor with a polytetrafluoroethylene liner, and then put the reactor into a forced air drying oven, first heat the reactor to 170-200 ° C, keep it warm for 0-60 minutes, then cool it to 160 ° C, keep it warm for 5 hours, take it out and cool it naturally to room temperature, wash the product after the reaction until it is neutral, place it in a drying oven at 80 ° C for 8 hours, grind and sieve the dried powder to obtain (Bi 0.5 Na 0.5 )TiO3 powder.
[0011] Preferably, in step 3, weigh (Bi 0.5 Na 0.5 ) The molar percentage of TiO3 powder is 0.50 mol%, and the chemical composition of the AST powder is TiO2: Al2O3: SiO2 = 3: 4: 9 molar ratio. 0.998 La 0.002 )The proportion of TiO3 is 6% by mole.
[0012] Preferably, in step 4, 6% by mass of polyvinyl alcohol and 2% by mass of liquid paraffin are added to the powder ball-milled in step 3 for granulation. The granulated powder is sieved and placed in a mold and pressed at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
[0013] Preferably, in step 5, the green body obtained in step 4 is placed in a box furnace for debinding, and the heating rate is 2°C / min at 600 ○C for 2 hours, and then cooled to room temperature with the furnace; the green billet after debinding was placed in a high temperature box furnace at 4 ○ The heating rate was increased to 900 C / min. ○ C for 1 h, then ○ C / min and the temperature is raised to sintering temperature 1320~1350 ○ C, keep warm for 15 to 120 minutes, then cool to room temperature with the furnace to obtain (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
[0014] Preferably, in step 1, the calcination temperature is 1250 ○ C Preferably, in step 2, the concentration of the NaOH solution is 12 mol / l, and the first stage heating temperature of the two-stage hydrothermal method is 180° C., and the insulation time is 30 minutes.
[0015] Preferably, in step 5, the green body after debinding is placed in a high temperature box furnace for 4 ○ The heating rate was increased to 900 C / min. ○ C for 1 h, then ○ C / min to the sintering temperature of 1330 ○ C, keep warm for 30 minutes.
[0016] Beneficial effects: Compared with the prior art, the present invention can achieve the following technical effects: 1. The present invention obtains (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic material has low room temperature resistivity and high Curie temperature. The room temperature resistivity, lift-to-resistance ratio and Curie temperature are 66.20 Ω∙cm, 2.57×10 5 and 148 ○ C, has good electrical properties.
[0017] 2. The preparation method of the present invention is to synthesize sodium bismuth titanate powder by two-stage heating hydrothermal method and (Ba 1-x La x)TiO3 powder, Mn(NO3)2 aqueous solution and sintering aid AST powder are mixed and then granulated, formed, debinded and sintered, which avoids the problem of insufficient dispersion of ceramic powder synthesized by solid phase reaction method and insufficient uniformity of chemical composition during the preparation of ceramic materials.
[0018] 3. The method of the present invention has low temperature, low cost, environmental friendliness, simple process and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The present invention adopts two-stage heating hydrothermal method to synthesize (Bi 0.5 Na 0.5 )SEM image of TiO3 powder.
[0020] Figure 2 The (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )XRD patterns of O3 ceramics. (y = 0.0000, 0.0025, 0.0050, 0.0075, 0.0100).
[0021] Figure 3 The (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )Dielectric constant-temperature curve of O3 ceramics.
[0022] Figure 4 The (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )Resistivity-temperature curves of O3 ceramics. (y = 0.0000, 0.0025, 0.0050, 0.0075, 0.0100).
[0023] Figure 5 The present invention is sintered under different sintering temperatures and different heat preservation times (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005)(Ti 0.9996 Mn 0.0004 )Room temperature resistivity of O3 ceramics.
[0024] Figure 6 For the present invention in 1330 ○ C was sintered for 0.5 hours to obtain (Ba 1-x La x )Electrical properties of TiO3 ceramics. (x = 0.001, 0.002, 0.003, 0.004). DETAILED DESCRIPTION
[0025] The present invention will be further described in detail below in conjunction with the accompanying drawings.
[0026] The present invention provides a high Curie temperature and low resistance lead-free thermistor ceramic, the chemical formula of which is (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3; the value range of x is 0.001 ≤ x ≤ 0.004, and the value range of y is 0.001 ≤ y ≤ 0.0075.
[0027] The present invention also discloses a method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic, which comprises the following steps: Step 1: Using BaCO3, TiO2, and La2O3 as raw materials, a solid phase reaction synthesis method was used to prepare (Ba 1-x La x )TiO3 powder; Step 2: Using Bi(NO3)3·5H2O, Ti(OC4H9)4 and NaOH as raw materials, a two-stage heating hydrothermal reaction method was used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder; Step 3: Follow (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio Weigh the (Ba 1-x La x )TiO3 powder, (Bi 0.5 Na 0.5 )TiO3 powder and Mn(NO3)2, and mixed with AST powder and added with anhydrous ethanol for ball milling, and then dried and ground; Step 4: adding polyvinyl alcohol and liquid paraffin to the ball-milled powder in step 3 to granulate, and placing the granulated powder into a mold and pressing it into a green body; Step 5: Place the green body obtained in step 4 into a box furnace for debinding and sintering to obtain (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet The specific embodiments are as follows: Embodiment 1: Step 1: BaCO3, TiO2, La2O3 are used as raw materials and synthesized by solid phase reaction method (Ba 0.998 La 0.002 )TiO3 powder. According to (Ba 0.998 La 0.002 )TiO3 stoichiometric ratio Weigh the above raw materials into a ball mill, and add anhydrous ethanol in a volume ratio of raw materials: anhydrous ethanol = 1:1 for ball milling. The speed of the ball mill is 300 r / min, and the ball milling time is 6 hours. After ball milling, the slurry is placed in an 80 ℃ oven to dry, then ground, sieved, and calcined. The calcination temperature is 1250 ℃, the heat preservation time is 2 hours, and then cooled to room temperature with the furnace.
[0028] Step 2: Using bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), tetrabutyl titanate (Ti(OC4H9)4) and sodium hydroxide (NaOH) as raw materials, a two-stage heating hydrothermal reaction method was used to synthesize sodium bismuth titanate ((Bi 0.5 Na 0.5 )TiO 3, BNT for short) powder. According to the molar ratio of Bi:Ti = 1:2, bismuth nitrate was dissolved in a dilute nitric acid solution (the volume ratio of ionized water to nitric acid was 1:1), stirred for 10 minutes, and a clear and transparent solution a was obtained. According to the molar ratio of Bi:Ti = 1:2, tetrabutyl titanate was dissolved in anhydrous ethanol, stirred until clear and transparent, and then added to solution a to obtain solution b. According to the concentration of 12 mol / l, NaOH was dissolved in deionized water, stirred for 40 minutes, and a clear and transparent aqueous solution was obtained, which was then added to solution b, and stirred for another 30 minutes to obtain a light yellow precursor solution. The precursor solution was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor was placed in a blast drying oven. A two-stage heating hydrothermal method was used to synthesize (Bi 0.5 Na 0.5)TiO3 powder. First, heat the reactor to 180 ℃ and keep it warm for 30 minutes, then cool it to 160 ℃ and keep it warm for 5 hours. After that, take the reactor out of the drying oven and cool it naturally to room temperature. Wash the product after the reaction until it is neutral, then place it in an 80 ℃ drying oven and dry it for 8 hours. Grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.
[0029] Step 3: Follow (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio weigh (Ba 0.998 La 0.002 )TiO3, BNT powder (where y = 0.0025, 0.0050, 0.0075, 0.010) and Mn(NO3)2, and then according to AST and (Ba 0.998 La 0.002 )TiO3 ratio is 6% molar ratio. Weigh the prefabricated AST powder (AST chemical composition is TiO2: Al2O3: SiO2= 3: 4: 9 molar ratio), put it into the ball mill jar in turn, and add anhydrous ethanol according to the volume ratio of raw material: anhydrous ethanol = 1:1 for ball milling. The speed of the ball mill is 300 r / min, and the ball milling time is 6 h. After ball milling, the slurry is placed in an oven at 80 ℃ for drying, and then ground in a mortar.
[0030] Step 4: Add 6% by mass of polyvinyl alcohol (PVA) and 2% by mass of liquid paraffin to the ground powder for granulation and sieve. Put the granulated powder into a mold and press it at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
[0031] Step 5: Place the green body in a box furnace for debinding, heating at a rate of 2 °C / min at 600 ○ C for 2 hours, and then cool to room temperature. ○ The heating rate was increased to 900 C / min. ○ C for 1 hour, then at 5 ○ The rate was increased to 1330 C / min ○ C for 30 minutes for sintering, and then cooled to room temperature with the furnace to obtain (Ba 0.998-y La 0.002 (Bi 0.5Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet, where y = 0.0025, 0.0050, 0.0075, 0.010.
[0032] The (Bi 0.5 Na 0.5 )The crystal structure of TiO3 powder is a single rhombohedral phase (Bi 0.5 Na 0.5 )TiO3, whose particles are aggregates composed of approximately 50 nm cubes with an average size of 450 nm (see Figure 1 ) Doping (Bi 0.5 Na 0.5 ) Four kinds of TiO3 powders (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheets are composed of a single tetragonal perovskite phase (see Figure 2 ). With (Bi 0.5 Na 0.5 )TiO3 molar ratio increases, the XRD diffraction peak gradually shifts to the right, indicating that (Bi 0.5 Na 0.5 )TiO3 solid dissolves into the BaTiO3 lattice. In addition, as (Bi 0.5 Na 0.5 ) As the TiO3 molar ratio increases, the Curie temperature gradually increases (see Figure 3 ), and the room temperature resistivity also increases (see Figure 4 When y = 0.0025, the room temperature resistivity of the ceramic is 77.29 Ω∙cm, and the lift-to-resistance ratio ( ρ max / min ) is 3.40×10 4 , and the Curie temperature is 140 °C. When y = 0.005, the room temperature resistivity of the ceramic is 66.20 Ω∙cm, and the lift-to-resistance ratio is 2.57×10 5 , Curie temperature is 148 ℃. When y = 0.0075, the room temperature resistivity of the ceramic is 18803.00 Ω∙cm, and the lift-to-resistance ratio is 1.50×10 1 , the Curie temperature is 150 ℃. When y = 0.010, the Curie temperature of the ceramic is 151 ℃, its room temperature resistivity is 61644.1 Ω∙cm, and there is no PTCR effect (see Figure 4 ). Therefore, y is preferably set to 0.005.
[0033] Embodiment 2: Step 1: BaCO3, TiO2, La2O3 are used as raw materials and synthesized by solid phase reaction method (Ba 0.998 La 0.002 )TiO3 powder. According to (Ba 0.998 La 0.002 )TiO3 stoichiometric ratio Weigh the above raw materials and put them into a ball mill according to the volume ratio of raw materials: anhydrous ethanol = 1:1. The speed of the ball mill is 300 r / min, and the ball milling time is 6 hours. After ball milling, the slurry is placed in an 80 ℃ oven to dry, then ground, sieved, and calcined. The calcination temperature is 1250 ℃, the heat preservation time is 2 hours, and then cooled to room temperature with the furnace.
[0034] Step 2: Using bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), tetrabutyl titanate (Ti(OC4H9)4) and sodium hydroxide (NaOH) as raw materials, sodium bismuth titanate ((Bi(OC4H9)4)) was synthesized by a two-stage heating hydrothermal method. 0.5 Na 0.5 )TiO 3, BNT for short) powder. According to the molar ratio of Bi:Ti = 1:2, bismuth nitrate was dissolved in a dilute nitric acid solution (the volume ratio of ionized water to nitric acid was 1:1), stirred for 10 minutes, and a clear and transparent solution a was obtained. According to the molar ratio of Bi:Ti = 1:2, tetrabutyl titanate was dissolved in anhydrous ethanol, stirred until clear and transparent, and then added to solution a to obtain solution b. According to the concentration of 12 mol / l, NaOH was dissolved in deionized water, stirred for 40 minutes, and a clear and transparent aqueous solution was obtained, which was then added to solution b, and then stirred for another 30 minutes to obtain a light yellow precursor solution. The precursor solution was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor was placed in a blast drying oven. A two-stage heating hydrothermal method was used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder. First, heat the reactor to 180 ℃ and keep it warm for 30 minutes, then cool it to 160 ℃ and keep it warm for 5 hours. After that, take the reactor out of the drying oven and cool it naturally to room temperature. Wash the product after the reaction until it is neutral, then place it in an 80 ℃ drying oven and dry it for 8 hours. Grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.
[0035] Step 3: Follow (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005 )(Ti 0.9996Mn 0.0004 )O3 stoichiometric ratio weigh (Ba 0.998 La 0.002 )TiO3, BNT powder and Mn(NO3)2, and then according to AST and (Ba 0.998 La 0.002 )TiO3 ratio is 6% molar. Weigh the pre-made AST powder, put it into the ball mill jar in turn, and add anhydrous alcohol for ball milling according to the volume ratio of raw material: anhydrous ethanol = 1:1. The speed of the ball mill is 300 r / min, and the ball milling time is 6 h. After ball milling, the slurry is placed in an oven at 80 ℃ for drying, and then ground in a mortar.
[0036] Step 4: Add 6% by mass of polyvinyl alcohol (PVA) and 2% by mass of liquid paraffin to the ground powder for granulation and sieve. Put the granulated powder into a mold and press it at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
[0037] Step 5: Place the green body in a box furnace for debinding, heating at a rate of 2 °C / min at 600 ○ C for 2 hours, and then cool to room temperature. ○ The heating rate was increased to 900 C / min. ○ C for 1 hour, then ○ The rate of C / min increased to 1320~1350 ○ C for 30 minutes for sintering, and then cooled with the furnace to obtain (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005 )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
[0038] 1320~1350 ○ The room temperature resistivity of ceramics sintered at C for 30 minutes is relatively low (see Figure 5 ), indicating that the sintering temperature window of this material system is relatively wide. ○ The room temperature resistivity of the ceramics obtained by heat preservation at 1330°C for 30 minutes were 77.0, 66.2, 78.3 and 87.5 Ω∙cm respectively. ○ The ceramic sintered at 1330°C has the lowest room temperature resistivity, so the sintering temperature is preferably set at 1330°C. ○ C.
[0039] Example 3 Step 1: BaCO3, TiO2, La2O3 are used as raw materials and synthesized by solid phase reaction method (Ba 0.998 La 0.002 )TiO3 powder. According to (Ba 0.998 La 0.002 )TiO3 stoichiometric ratio Weigh the above raw materials into a ball mill, and add anhydrous ethanol in a volume ratio of raw materials: anhydrous ethanol = 1:1 for ball milling. The speed of the ball mill is 300 r / min, and the ball milling time is 6 hours. After ball milling, the slurry is placed in an 80 ℃ oven to dry, then ground, sieved, and calcined. The calcination temperature is 1250 ℃, the heat preservation time is 2 hours, and then cooled to room temperature with the furnace.
[0040] Step 2: Using bismuth nitrate pentahydrate (Bi(NO3)3·5H2O), tetrabutyl titanate (Ti(OC4H9)4) and sodium hydroxide (NaOH) as raw materials, a two-stage heating hydrothermal reaction method was used to synthesize sodium bismuth titanate ((Bi 0.5 Na 0.5 )TiO 3, BNT for short) powder. According to the molar ratio of Bi:Ti = 1:2, bismuth nitrate was dissolved in a dilute nitric acid solution (the volume ratio of ionized water to nitric acid was 1:1), stirred for 10 minutes, and a clear and transparent solution a was obtained. According to the molar ratio of Bi:Ti = 1:2, tetrabutyl titanate was dissolved in anhydrous ethanol, stirred until clear and transparent, and then added to solution a to obtain solution b. According to the concentration of 12 mol / l, NaOH was dissolved in deionized water, stirred for 40 minutes, and a clear and transparent aqueous solution was obtained, which was then added to solution b, and stirred for another 30 minutes to obtain a light yellow precursor solution. The precursor solution was placed in a stainless steel reactor with a polytetrafluoroethylene liner, and the reactor was placed in a blast drying oven. A two-stage heating hydrothermal method was used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder. First, heat the reactor to 180℃ and keep it warm for 30 minutes, then cool it to 160℃ and keep it warm for 5 hours. After that, take the reactor out of the drying oven and cool it naturally to room temperature. Wash the product after the reaction until it is neutral, then place it in a drying oven at 80℃ and dry it for 8 hours. Grind and sieve the dried powder to obtain a light yellow (Bi 0.5 Na 0.5 )TiO3 powder.
[0041] Step 3: Follow (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005 )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio weigh (Ba0.998 La 0.002 )TiO3, BNT powder and Mn(NO3)2, and then according to AST and (Ba 0.998 La 0.002 )TiO3 ratio is 6% molar. Weigh the pre-made AST powder, put it into the ball mill jar in turn, and add anhydrous alcohol for ball milling according to the volume ratio of raw material: anhydrous ethanol = 1:1. The speed of the ball mill is 300 r / min, and the ball milling time is 6 h. After ball milling, the slurry is placed in an oven at 80 ℃ for drying, and then ground in a mortar.
[0042] Step 4: Add 6% by mass of polyvinyl alcohol (PVA) and 2% by mass of liquid paraffin to the ground powder for granulation and sieve. Put the granulated powder into a mold and press it at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
[0043] Step 5: Place the green body in a box furnace for debinding, heating at a rate of 2 °C / min at 600 ○ C for 2 hours, and then cool to room temperature. ○ The heating rate was increased to 900 C / min. ○ C for 1 hour, then ○ The rate of C / min increased to 1320~1350 ○ C for 15 to 120 minutes for sintering, and then cooling with the furnace to obtain (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005 )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
[0044] 1320~1350 ○ The room temperature resistivity of ceramics sintered within the C range increases with the increase of holding time (see Figure 5 ). At 1330 ○ The room temperature resistivity of the ceramics obtained by holding at 15, 30, 60 and 120 minutes at 370°C was 97.9, 66.2, 396.8 and 2766.2 Ω∙cm, respectively. Among them, the ceramics held at 30 minutes showed the lowest room temperature resistivity, so the sintering holding time was preferably 30 minutes.
[0045] Comparative Example 1: Step 1: Prepare (Ba) by solid phase reaction synthesis 0.998 La 0.002 )TiO3 powder. According to (Ba0.998 La 0.002 )BaCO3, TiO2, and La2O3 are weighed as raw materials and placed in a ball mill in sequence. Anhydrous ethanol is added to the ball mill in a volume ratio of raw materials: anhydrous ethanol = 1:1 for ball milling. The speed of the ball mill is 300 r / min, and the ball milling time is 6 hours. After ball milling, the slurry is placed in an oven at 80 ℃ for drying, then ground, sieved, and calcined. The calcination temperature is 1250 ℃, the insulation time is 2 hours, and then cooled to room temperature with the furnace.
[0046] Step 2: Follow (Ba 0.998 La 0.002 )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio weigh (Ba 0.998 La 0.002 )TiO3 powder and Mn(NO3)2, and then according to AST and (Ba 0.998 La 0.002 )TiO3 ratio is 6% molar ratio. Weigh the pre-made AST powder, put it into the ball mill jar in turn, and add anhydrous ethanol according to the volume ratio of raw material: anhydrous ethanol = 1:1 for ball milling. The speed of the ball mill is 300 r / min, and the ball milling time is 6 hours. After ball milling, place the slurry in an oven at 80 ℃ for drying, and then grind it in a mortar.
[0047] Step 3: Add 6% by mass of polyvinyl alcohol (PVA) and 2% by mass of liquid paraffin to the ground powder for granulation and sieve. Put the granulated powder into a mold and press it at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
[0048] Step 4: Place the green body in a box furnace for debinding, heating at a rate of 2 °C / min at 600 ○ C for 2 hours, and then cool to room temperature. ○ The heating rate was increased to 900 C / min. ○ C for 1 h, and then at 5 ○ C / min to 1330 ○ C, keep warm for 30 minutes for sintering, and then cool to room temperature with the furnace to obtain (Ba 0.998 La 0.002 )(Ti 0.9996 Mn 0.0004 )O3 ceramics.
[0049] The obtained 0.998 La 0.002 )(Ti0.9996 Mn 0.0004 )O3 ceramics are composed of a single tetragonal perovskite phase (see Figure 2 , y = 0.0000), its Curie temperature is 128 ○ C (see Figure 3 ), the room temperature resistivity is 24.19 Ω∙cm, and the lift-to-resistance ratio is 5.14×10 3 (See Figure 4 ).
[0050] Compared with Comparative Example 1, although a trace amount of BNT is added (Ba 0.998-y La 0.002 (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramics have a room temperature resistivity increase, but the Curie temperature increases significantly. Especially at 1330 ○ C for 30 minutes (Ba 0.993 La 0.002 (Bi 0.5 Na 0.5 ) 0.005 )(Ti 0.9996 Mn 0.0004 ) The Curie temperature of O3 ceramics is as high as 148 ○ C (see Figure 3 ), while its room temperature resistivity and lift-to-resistance ratio are 66.20 Ω∙cm and 2.57×10 5 (See Figure 6 ), with good comprehensive PTCR performance, indicating that the barium titanate-based lead-free thermistor ceramics prepared by the present invention have broad application prospects in starting switch elements, overcurrent and overheating protection elements, and temperature sensors for sensing thermal information. Although the specific embodiments of the present invention are described above, those skilled in the art should understand that these are only examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of the present invention is limited only by the appended claims.
Claims
1. A high Curie temperature and low resistance lead-free thermistor ceramic, characterized in that: The chemical formula of the thermosensitive ceramic is (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3; the value range of x is 0.001 ≤ x ≤ 0.004, and the value range of y is 0.001 ≤ y ≤ 0.0075.
2. A method for preparing a high Curie temperature and low resistance lead-free thermistor ceramic as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Using BaCO3, TiO2, and La2O3 as raw materials, a solid phase reaction synthesis method was used to prepare (Ba 1-x La x )TiO3 powder; Step 2: Using Bi(NO3)3·5H2O, Ti(OC4H9)4 and NaOH as raw materials, a two-stage heating hydrothermal reaction method was used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder; Step 3: Follow (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 stoichiometric ratio Weigh the (Ba 1-x La x )TiO3 powder, (Bi 0.5 Na 0.5 )TiO3 powder and Mn(NO3)2, and mixed with AST powder and added with anhydrous ethanol for ball milling, and then dried and ground; Step 4: adding polyvinyl alcohol and liquid paraffin to the ball-milled powder in step 3 to granulate, and placing the granulated powder into a mold and pressing it into a green body; Step 5: Place the green body obtained in step 4 into a box furnace for debinding and sintering to obtain (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
3. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 2, characterized in that: In step 1, the solid phase reaction synthesis method is used to prepare (Ba 1-x La x )TiO3 powder process is: according to (Ba 1-x La x )TiO3 stoichiometric ratio, weigh the raw material, and put the raw material and anhydrous ethanol into a ball mill at a volume ratio of 1:1, and after ball milling, place the slurry in an oven to dry, grind, sieve and calcine, the calcination temperature is 1200~1300 ℃, the heat preservation time is 2 hours, and then cool to room temperature with the furnace to obtain (Bi 0.5 Na 0.5 )TiO3 powder.
4. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 2, characterized in that: In step 2, the two-stage heating hydrothermal reaction method is used to synthesize (Bi 0.5 Na 0.5 )TiO3 powder is prepared by weighing Bi(NO3)3·5H2O and Ti(OC4H9)4 at a molar ratio of Bi:Ti = 1:2, dissolving Bi(NO3)3·5H2O in a dilute nitric acid solution to obtain solution a; dissolving Ti(OC4H9)4 in anhydrous ethanol and adding the solution to solution a to obtain solution b; dissolving NaOH in deionized water at a concentration of 6-14 mol / l to obtain a NaOH solution; Adding solution b to the NaOH solution to obtain a precursor solution; The precursor solution was placed in a stainless steel reactor with a polytetrafluoroethylene lining, and then the reactor was placed in a forced air drying oven. The reactor was first heated to 170-200 °C and kept warm for 0-60 minutes, then cooled to 160 °C, kept warm for 5 hours, taken out and naturally cooled to room temperature. The product after the reaction was washed to neutrality, placed in an 80 °C drying oven for 8 hours, and the dried powder was ground and sieved to obtain (Bi 0.5 Na 0.5 )TiO3 powder.
5. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 2, characterized in that: In step 3, weigh (Bi 0.5 Na 0.5 )TiO3 powder has a molar percentage of 0.50 mol%, and the chemical composition of the AST powder is TiO2: Al2O3: SiO2 = 3: 4: 9 molar ratio. 0.998 La 0.002 )The proportion of TiO3 is 6% by mole.
6. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 2, characterized in that: In step 4, 6% by mass of polyvinyl alcohol and 2% by mass of liquid paraffin are added to the ball-milled powder in step 3 for granulation. The granulated powder is sieved and placed in a mold and pressed at 2.0 MPa to form a ceramic green body with a diameter of 12 mm and a thickness of 1.2 mm.
7. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 2, characterized in that: In step 5, the green body obtained in step 4 is placed in a box furnace for debinding, and the heating rate is 2 °C / min at 600 ○ C for 2 hours, and then cooled to room temperature with the furnace; the green billet after debinding was placed in a high temperature box furnace at 4 ○ The heating rate was increased to 900 C / min. ○ C for 1 h, then ○ C / min and the temperature is raised to sintering temperature 1320~1350 ○ C, keep warm for 15 to 120 minutes, then cool to room temperature with the furnace to obtain (Ba 1-x-y La x (Bi 0.5 Na 0.5 ) y )(Ti 0.9996 Mn 0.0004 )O3 ceramic sheet.
8. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 3, characterized in that: In step 1, the calcination temperature is 1250 ○ C.
9. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 4, characterized in that: In step 2, the concentration of the NaOH solution is 12 mol / l, and the first heating temperature of the two-stage hydrothermal method is 180° C., and the holding time is 30 minutes.
10. The method for preparing the high Curie temperature and low resistance lead-free thermistor ceramic according to claim 7, characterized in that: In step 5, the green billet after debinding is placed in a high temperature box furnace for 4 ○ The heating rate was increased to 900 C / min. ○ C for 1h, then ○ C / min to the sintering temperature of 1330 ○ C, keep warm for 30 minutes.
Citation Information
Patent Citations
Semiconductor porcelain composition and method of producing the same
CN101213155A
Method for preparing high Curie point leadless PTC ceramic resistance material
CN101224979A
Thermally stable leadless high temperature piezoelectric ceramic and preparing method thereof
CN101234900A
Semiconductor ceramic composition and ptc thermistor
CN107043252A
Method for manufacturing semiconductor porcelain composition
JP2013144637A